"Å få eit forhold til å fungere er ganske hard jobbing" - Danielsen, Hilde (Tidsskrift for kulturforskning, 2008)
Communication, Gender and Love in Heterosexual Relationships. The tension between understanding couple relationships as "given as they are" or possible to develop, control and change is the subject for this article. The analysis is based upon how heterosexual couples talk about love, communication and gender in qualitative interviews. Love is understood as work which needs investment, in opposition to be "in love" it is talked about as a choice which needs action to be kept alive. To work with the relationship becomes a new demand and form of mutual responsibility for modern couples. Communication is given an essential value as glue in the relationship, both as a means of avoiding misunderstandings and as a tool to create and nurture intimacy and positive change. Stereotypical and possible essentialist views of gender - such as women are better talkers and men are more solution-minded - are important argumentative resources in understanding difficulties regarding love and communication for the couples. Gender is however not used as defining the truth about the partners, but as a starting point for a discussion about issues in the relationship. The therapeutic ethos about possible change and growth in personal relationships fronted through the idea love as work is more important for the couples than complementary ideas about gender